Synthesis and glycosidation of building blocks of D-altrosamine - Novakova, Mariya; Das, Anupama; Alex, Catherine; Demchenko, Alexei V. (Frontiers in Chemistry, 2022)
Presented herein is a streamlined synthesis of building blocks of a rare sugar D-altrosamine. Also investigated was glycosylation of different glycosyl acceptors with differentially protected altrosamine donors. High facial stereoselectivity was achieved with 3-O-picoloyl donors and reactive glycosyl acceptors via the H-bond-mediated aglycone delivery (HAD) pathway. In contrast, glycosidations of altrosamine donor equipped with 3-O-benzoyl group were poorly stereoselective